Synthesis and Crystal Structure of Two Cu II ‐benzene‐1,2,4,5‐tetracarboxylates with Three‐Dimensional Open Frameworks - Köferstein, Roberto; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2014)
Two new three‐dimensional frameworks with zeolite‐like channels were prepared in the presence of 1,6‐diaminohexane. Cu 1.5 (H 3 N–(CH 2 ) 6 –NH 3 ) 0.5 [C 6 H 2 (COO) 4 ] · 5H 2 O ( 1 ) crystallizes in the triclinic space group P $\bar{1}$ with a = 772.56(7), b = 1110.36(7), c = 1111.98(8) pm, α = 98.720(7)°, β = 108.246(9)°, and γ = 95.559(7)°. Cu 2 (H 3 N–(CH 2 ) 6 –NH 3 ) 0.5 (OH)[C 6 H 2 (COO) 4 ] · 3H 2 O ( 2 ) crystallizes in the monoclinic space group P2 / c with a = 1159.34(11), b = 1059.44(7), c = 1582.2(2) pm, and β = 106.130(11)°. The Cu 2+ coordination polyhedra are connected by [C 6 H 2 (COO) 4 ] 4– anions to yield three‐dimensional frameworks with wide centrosymmetric channel‐like voids. Complex 1 reveals voids extending along [100] with diagonals of 900 pm and 300 pm, whereas in complex 2 the diagonal of the nearly rectangular crossection of the channels extending parallel to [001] is 900 pm. The negative excess charges of the frameworks are compensated by [H 3 N–(CH 2 ) 6 –NH 3 ] 2+ cations, which occupy the voids along with water molecules. The [H 3 N–(CH 2 ) 6 –NH 3 ] 2+ cations are not connected to Cu 2+ and have served as templates.